Comparison of the nest organization and soil properties of Microcerotermes pakistanicus and Odontotermes obesus constructions in the Western Ghats, India - Harit, A.K.; Ramasamy, E.V.; Babu, N.; Pillai, R.M.J.; Bottinelli, N.; Cheik, S.; Jouquet, P. (DataSuds, 2021)
Dataset describing the soil properties (termite nests and sheetings) and nest organization of two common species in Kerala, India: Odontotermes obesus and Microcerotermes pakistanicus. Soil properties included: pH, electrical conductivity (uS cm-1), soil particle size distribution (clay, silt, sand, in %), and C (%), N (%), anion (Cl, F, NO3, SO4, in ppm) and cation (Na, K, Mg, Ca, in ppm) contents . Nest organization was measured using X-ray computed tomography and measures consisted in the measure of the total soil macroporosity (%), pore density (number mm-3), mean diameter (mm) and the probability gamma.